Internal Communication in a Digital Environment: A Research Study on Businesses - PELTEKOĞLU, ZEYNEP FİLİZ (MARMARA UNIV, FAC COMMUNICATION, 2020)
Corporate productivity, corporate loyalty and corporate reputation, as well as the right to information of the employees all foster the need for internal communication For this reason, companies need to carry out effective communication techniques not only with their external stakeholders, but within the company itself as well. The fact that every communication tool evolves into a tool and method of public relations necessitates the need for companies to include digital communication technologies into their public relations strategies. There is also a correlation between the structure of said companies and the way they conduct public relations. In this study, a field research was carried out with the human resources units of 70 companies of different sizes operating in Cerkezkoy in order to understand the relationship between the changes in communication technologies and the internal communication techniques employed by these enterprises, as well as the relationship between the size of a company and the communication tools and strategies they choose to employ. Both quantitative and qualitative research methods were used throughout the study. The findings of the study reveal that digital communication is widely used in internal communications and also that the utilization of social media as a communication tool varied between companies of different sizes.
Keywords: Public Relations; Internal Communication; Digital Communication; Social Networks; Social Media